The putative involvement of actin‐binding proteins and cytoskeleton proteins in pathological mechanisms of ketamine cystitis—Revealed by a prospective pilot study using proteomic approaches - Yang, Hsueh‐Hui; Zhai, Wei‐Jun; Kuo, Hann‐Chorng (Proteomics. Clinical applications, 2017)
Purpose Ketamine‐induced cystitis (KC) among chronic ketamine young abusers has increased dramatically and it has brought attention for Urologists. The underlying pathophysiological mechanism(s) of KC is still unclear. Therefore, the purpose of this study is to elucidate the possible pathophysiological mechanism(s) of KC through proteomic techniques. Experimental design Bladder tissues are obtained from seven patients with KC, seven patients with interstitial cystitis/bladder pain syndrome, and five control subjects who underwent video‐urodynamic study followed by augmentation enterocystoplasty to increase bladder capacity. 2DE/MS/MS‐based approach, functional classifications, and network analyses are used for proteomic and bioinformatics analyses and protein validation is carried out by Western blot analysis. Results Among the proteins identified, bioinformatics analyses revealed that several actin binding related proteins such as cofilin‐1, myosin light polypeptide 9, filamin A, gelsolin, lamin A are involved in the apoptosis. Besides, the contractile proteins and cytoskeleton proteins such as myosin light polypeptide 9, filamin A, and calponin are found downregulated in KC bladders. Conclusions and clinical relevance Increased apoptosis in KC might be mediated by actin‐binding proteins and a Ca2+‐activated protease. Rapid detrusor contraction in KC might be induced by contractile proteins and cytoskeleton proteins.